Investigation of hydrogeochemical processes and groundwater quality of the Kakontwe aquifers in Ndola, Zambia - Gomo, Benard Tembo (University of the Free State, 2018)
The study was aimed at investigating the hydrogeochemical processes of the Kakontwe aquifers in Ndola Zambia. The objective of the study was the characterisation the ground-water quality and related hydrogeochemical processes in the study area as well as to as-sess the quality of the groundwater to determine its suitability for industrial and agricul-tural uses. The researcher did not assess domestic water suitability due to limitations in analysis parameters. The researcher collected groundwater samples for Laboratory analysis in 2017 and 2018. Sixty-Five samples were collected from the 33 locations during the two years for labora-tory analysis for water quality assessment. Classification of the main water types and hy-drogeochemical processes assessment and data interpretation was done using complementary tools such as stoichiometry and bivariate analysis, statistical analysis (hi-erarchical cluster analysis and principal component analysis), Gibbs Diagrams and Satu-ration indices. The average groundwater level recorded was 7.3 mbgl (approximate 1261 masl) with a range from 2.6 mbgl to 16.99 mbgl and correlation showed that the groundwater flows towards the nearby stream. The average ion balance error shows that the samples analysis is generally accepted as was within the acceptable range of below 5%. Major ions concentration in the groundwater for both 2017and 2018 data were recorded in the following order; HCO3- > Ca²+ > CO3-> Mg²+ > SO42- > Cl- > K+ >Na+. The main water types assessed in the study area were calcium bicarbonate. Chloride was also observed to have a significant influence in the process even though the chloride could not be associated with the predicted weathering process. The Chloride can be predicted to be from external sources causing accumulation in the system. The main hydrogeochem-ical processes that were inferred to be influencing the groundwater chemistry and quality are carbonate dissolution and silicate weathering. A Langelier Saturation Index estimated indicated the saturated water with calcium car-bonate and scale forming and corrosion could occur in the industrial equipment using the water in the study area. Treatment of the water before using for industrial purposes espe-cially in boilers and heating equipment is therefore advisable. Based on the calculated Kelly’s Ratio, the Kakontwe aquifer water showed lower levels of sodium ions and was classified as Good/Excellent for irrigation purposes. The Wilcox plots showed a Low-Risk classification on the Sodium (Alkali) hazard scale while the values for the salinity hazard showed a Medium Risk further confirming the suitability of the groundwater for irriga-tion use. The study also demonstrated the value of utilising various assessment tools as comple-mentary techniques to improve the understanding of hydrogeochemical processes, and its influence on progression of groundwater chemistry and quality.
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2018
Keywords: Hydrogeochemical; Groundwater chemistry; Groundwater quality; Hydrogeochemical processes; Principal component analysis; Water types